Moderate levels of chronic mood disturbance are associated with increased cognitive complexity about the self. - MacLeod, A; Williams, J (1991)
Despite its status as a general assumption, the idea that mood disturbance is associated with reduced complexity of cognitive representations has received little in the way of empirical support. It is suggested that this may arise because of a failure to make distinctions concerning the severity and type of mood disturbance, as well as not being specific about what the representations actually refer to. Using repertory grid methodology (Bieri et al., 1966) with a group of moderately mood-disturbed 'worriers', results showed that this group are significantly more complex than matched controls, but only for representations concerned with themselves. Moreover, this was related to chronic rather than current mood disturbance. The results are interpreted as indicating that cognitive complexity may follow an inverted-U pattern, where the self-representations of severely mood-disturbed and control subjects, although differing in valence, are similar in their lack of complexity. On the other hand, those who are chronically but moderately disturbed are, as a result of their ongoing tendency towards introspection, more complex in their self-representations. Possible implications for vulnerability to emotional disorder are discussed.